Textual Competence in Translating Poetry: Classroom Experiences Practice Sri Handayani (ELATICS JOURNAL, 2023)
This research was aimed at describing the textual competences taught in the literary translation course, identifying, and analysing the activities done by the lecturers in the process of teaching literary translation. The research employed a qualitative method by applying a case study as a research design. There were two lecturers and 85 sixth semester students of Translation Literary Works course who had participated in this research. The data were collected through observation and questionnaire ways to explore the information as the data. The results of the research showed that the genre and topical knowledge could be trained with the techniques used by the lecturers in translating literary works such as (1) introducing and practicing the translation in different genres; (2) focusing the translation activities in a certain genre; and (3) applying reading for effect.